Enzymatic catalysis of anti-Baldwin ring closure in polyether biosynthesis. - Hotta, K; Chen, X; Paton, R; Minami, A; Li, H; Swaminathan, K; Mathews, I; Watanabe, K; Oikawa, H; Houk, K; Kim, C (2012)
Polycyclic polyether natural products have fascinated chemists and biologists alike owing to their useful biological activity, highly complex structure and intriguing biosynthetic mechanisms. Following the original proposal for the polyepoxide origin of lasalocid and isolasalocid and the experimental determination of the origins of the oxygen and carbon atoms of both lasalocid and monensin, a unified stereochemical model for the biosynthesis of polyether ionophore antibiotics was proposed. The model was based on a cascade of nucleophilic ring closures of postulated polyepoxide substrates generated by stereospecific oxidation of all-trans polyene polyketide intermediates. Shortly thereafter, a related model was proposed for the biogenesis of marine ladder toxins, involving a series of nominally disfavoured anti-Baldwin, endo-tet epoxide-ring-opening reactions. Recently, we identified Lsd19 from the Streptomyces lasaliensis gene cluster as the epoxide hydrolase responsible for the epoxide-opening cyclization of bisepoxyprelasalocid A to form lasalocid A. Here we report the X-ray crystal structure of Lsd19 in complex with its substrate and product analogue to provide the first atomic structure-to our knowledge-of a natural enzyme capable of catalysing the disfavoured epoxide-opening cyclic ether formation. On the basis of our structural and computational studies, we propose a general mechanism for the enzymatic catalysis of polyether natural product biosynthesis.